2018
DOI: 10.1007/978-3-319-58316-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Characterization of Vibrotactile Interfaces

Abstract: While a standard approach is more or less established for rendering basic vibratory cues in consumer electronics, the implementation of advanced vibrotactile feedback still requires designers and engineers to solve a number of technical issues. Several off-the-shelf vibration actuators are currently available, having different characteristics and limitations that should be considered in the design process. We suggest an iterative approach to design in which vibrotactile interfaces are validated by testing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Such procedure results in verified, accurate data, which are especially important when using the device as a measurement and stimulation tool (e.g. in psychophysical experiments), allowing a better interpretation of results [31].…”
Section: B Characterization and Calibrationmentioning
confidence: 99%
“…Such procedure results in verified, accurate data, which are especially important when using the device as a measurement and stimulation tool (e.g. in psychophysical experiments), allowing a better interpretation of results [31].…”
Section: B Characterization and Calibrationmentioning
confidence: 99%
“…The original Soundplane was equipped with an actuators layer based on piezoelectric discs, while a software system for synthesizing vibrotactile feedback was developed, resulting in the HSoundplane prototype (where "H" stands for "haptic"), shown in Figure 10. The design of the haptic layer is described in detail in Papetti et al (2018); therefore, only essential information is reported here. In order to drive the piezo discs with standard audio signals, custom amplifying and routing electronics were designed.…”
Section: The Hsoundplanementioning
confidence: 99%
“…Several strategies have been developed to achieve localized vibrational feedback over a rigid surface. One can use actuators bonded to the surface and obtain localized vibrations within the area of the actuator [3]. This approach requires a considerable amount of actuators to operate over the whole surface and is affected by the effects of wave propagation *Project funded by the Swiss National Science Foundation (SNSF # 178972).…”
Section: Introductionmentioning
confidence: 99%